1985
DOI: 10.1177/0013916585175001
|View full text |Cite
|
Sign up to set email alerts
|

Social Cohesiveness, Territoriality, and Holiday Decorations

Abstract: Altman's territoriality theory was used as a framework for examining neighborhood attachment. We hypothesized that attachment would be manifested in interrelated patterns of neighboring behaviors, attitudes indicating that the block was a secondary territory, and individual and communal displays of holiday decorations. Design features of cul-de-sacs were hypothesized to contribute to greater degrees of block attachment on cul-de-sacs than on through streets. Attachment was assessed through interviews with fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 34 publications
3
64
0
7
Order By: Relevance
“…The findings of the present study indicate that respondents from the properties located on cul-de-sacs and local streets perceived a higher level of social cohesion compared to those from the arterials. This result is consistent with the findings of a previous study (Brown & Werner, 1985), suggesting that residents from close streets are more protective of their surroundings and are associated with higher levels neighbourhood cohesion, compared to the higher levels of hierarchy. Bivariate correlations.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of the present study indicate that respondents from the properties located on cul-de-sacs and local streets perceived a higher level of social cohesion compared to those from the arterials. This result is consistent with the findings of a previous study (Brown & Werner, 1985), suggesting that residents from close streets are more protective of their surroundings and are associated with higher levels neighbourhood cohesion, compared to the higher levels of hierarchy. Bivariate correlations.…”
Section: Resultssupporting
confidence: 92%
“…Evidence seems to suggest that there is a high degree of neighbouring behaviour on cul-de-sacs (Brown & Werner, 1985). Similarly, a previous study has indicated that residents living on high permeable streets have limited their activities in the use of property frontage and their exposure to the strangers (Appleyard & Lintell, 1972).…”
Section: Permeability and Social Cohesionmentioning
confidence: 89%
See 1 more Smart Citation
“…To be true, there is no general agreement among psychologists about the definition of each of these concepts. Attachment is at times treated as a synonym of identity (Brown and Werner 1985;Stedman 2002, p. 563), correlated with it (Williams 2002;Hernandez et al 2007, p. 311) or subsumed within it (Lalli 1992;Puddifoot 1995), occasionally in form of a prerequisite (Proshansky et al 1983, p. 60-61;Twigger-Ross and Uzzell 1996, p. 206). In other cases, both identity and attachment are instead conceptualized as components of a superordinate category, sense of place (Hay 1998, p. 7;Jorgensen and Stedman 2001, p. 233).…”
Section: Environmental Psychologymentioning
confidence: 99%
“…B. Brown & Werner, 1985;Sauter & Huettenmoser, 2008). Presence of functional spaces complementing the dwelling units, such as interactional and communal spaces, and other related social facilities (Huang, 2006;Kang, 2006;Sirgy & Cornwell, 2002) impacts the residents' quality of life (Sirgy & Cornwell, 2002;Sugiyama & Thompson, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%